Visual methods of processing survey data in social disciplines based on fuzzy logic - Grzegorz Śmigielski; Aleksandra Mreła; Oleksandr Sokolov; Mykoła Nedashkovskyy (Bulletin of the Polish Academy of Sciences: Technical Sciences, 2021)
All universities are responsible for assessing the quality of education. One of the required factors is the results of the students’ research. The procedure involves, most often, the preparation of the questionnaire by the staff, which is voluntarily answered by students; then, the university staff uses the statistical methods to analyze data and prepare reports. The proposed EQE method by the application of the fuzzy relations and the optimistic fuzzy aggregation norm may show a closer connection between the students’ answers and the achieved results. Moreover, the objects obtained by the application of the EQE method can be visualized by using the t-SNE technique, cosine between vectors and distances of points in five-dimensional space.